Performance of a Ge-doped optical fibre dosimeter for CT real-time measurements - Sarhan, H. G.; M. Saini, S.; M. Bahari, N.; Bradley, D. A.; Zubair, H. T.; Basaif, A.; Oresegun, A. A.; Abdul Rashid, H. A.; M. Noor, N. (Elsevier, 2023)
This study investigates the dosimetric characteristics of a real-time radioluminescence (RL) Ge-doped optical fiber sensor, model LS-1000, providing measurement of absorbed dose in terms of counts in use of a computed tomography (CT) system. A CT dose index head phantom has been used as the reference tool. The response of the LS-1000 sensor has been compared against that of two other forms of dosimeter - a RaySafe X2 CT sensor (an ionization chamber system) and a Black Piranha CT dose profiler (a point dose solid-state detector). The three dosimeters have been irradiated in each of five available holes within the CT dose index head phantom. The results show RL response at the position of the peripheral holes of around 250 counts/gate for a gate time of 10 ms, while at the position of the central hole the response was 80 counts/gate. The maximum dose rate for the RaySafe X2 CT sensor has been found to be 5 mGy/s while that observed for the CT dose profiler was 6 mGy/s. In respect of CT applications, this trial of the luminescence device demonstrates that the germanium-doped optical fiber device may offer a promising alternative to conventional dosimeters, also allowing measurements at high accuracy and precision.